(untitled) (Northern International Medical College Journal, 2017)
Background : Nephrotic syndrome (NS) is one of the most common renal diseases in children. The cause of idiopathic nephrotic syndrome is still unknown. Once the prevalence of minimal change nephritic syndrome occupied the three forth portion of the total renal pathology and most of them were steroid sensitive. But list of steroid insensitive nephritic syndrome become more longer today. Therefore renal biopsy is essential for histopathological diagnosis which guides the most accurate way for the treatment of such diseases. Objective : The objective of this study was to find out the pattern of renal histopathology of selected cases of Idiopathic nephritic syndrome. Materials and Method : This prospective study was conducted from January 2004 to December 2015 among children who were suffering from nephrotic syndrome admitted in Paediatric nephrology department, National Institute of Kidney Diseases and Urology(NIKDU), Dhaka. Renal biopsy were done who fulfil the inclusion criteria. Obtaining ultrasound-guided percutaneous renal biopsy specimens by means of an automated biopsy gun, were evaluated histopathologically under light and direct immunoflurescent(DIF) microscopy by an experienced histopathologist. Results : Total admitted childhood nephrotic syndrome during this period was 1512 and renal biopsy was done in 354 patient. Among the 354 children, histopathological findings were mesangial proliferative glomerulonephritis [MesPGN]was 92(25.98%),minimal change disease[MCD]was79 (22.32%), IgM nephropathy[IgMN]was69(19.49%), focal segmental glomerulosclerosis[FSGS] was 37(10.45%), membranoproliferative glomerulonephritis [MPGN] was 37(10.45%), IgA nephropathy [IgAN] was 20(5.65%),membranous nephropathy[MN] was 08(2.27%) and others were 12(3.39%). Conclusion : In this study we found that theselected patient for renal biopsy in the last 12 years showed that minimal change disease had been decreasing but the other histological types are increasing gradually such as mesangial proliferative glomerulonephritis, FSGS and IgM nephropathy. Northern International Medical College Journal Vol.8(1) July 2016: 165-169